Population Pharmacokinetic/Pharmacodynamic Modeling of Tumor Size Dynamics in Pembrolizumab‐Treated Advanced Melanoma. (29th November 2016) - Chatterjee, MS; Elassaiss‐Schaap, J; Lindauer, A; Turner, DC; Sostelly, A; Freshwater, T; Mayawala, K; Ahamadi, M; Stone, JA; de Greef, R; Kondic, AG; de Alwis, DP
Abstract : Pembrolizumab is a potent immune‐modulating antibody active in advanced melanoma, as demonstrated in the KEYNOTE‐001, ‐002, and ‐006 studies. Longitudinal tumor size modeling was pursued to quantify exposure‐response relationships for efficacy. A mixture model was first developed based on an initial dataset from KEYNOTE‐001 to describe four patterns of tumor growth and shrinkage. For subsequent analyses, tumor size measurements were adequately described by a single consolidated model structure that captured continuous tumor size with a combination of growth and regression terms, as well as a fraction of tumor responsive to therapy. This revised model structure provided a framework to efficiently evaluate the impact of covariates and pembrolizumab exposure. Both models indicated that exposure to the drug was not a significant predictor of tumor size response, demonstrating that the dose range evaluated (2 and 10 mg/kg every 3 weeks) is likely near or at the plateau of maximal response.